2018
DOI: 10.1016/s2468-2667(18)30051-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post-traumatic stress disorder on refugees' parenting and their children's mental health: a cohort study

Abstract: National Health and Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
143
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 35 publications
9
143
2
2
Order By: Relevance
“…As demonstrated in previous research, post-traumatic stress extends beyond the individual to family members and can be experienced as a common trauma in the family, where parents' reactions to traumatic experiences and the child's own perception of these experiences may affect the child's wellbeing and mental health [15]. Parental experience of traumatic stress may lead to a lack of consistency and stability in the family and has been associated with disconnected and insensitive parenting behaviour and harsh parenting styles [11,12,25,26]. Parental exposure to various forms of trauma has also been associated with an increased risk of violent behaviour and child abuse [27,28].…”
Section: Discussionmentioning
confidence: 96%
“…As demonstrated in previous research, post-traumatic stress extends beyond the individual to family members and can be experienced as a common trauma in the family, where parents' reactions to traumatic experiences and the child's own perception of these experiences may affect the child's wellbeing and mental health [15]. Parental experience of traumatic stress may lead to a lack of consistency and stability in the family and has been associated with disconnected and insensitive parenting behaviour and harsh parenting styles [11,12,25,26]. Parental exposure to various forms of trauma has also been associated with an increased risk of violent behaviour and child abuse [27,28].…”
Section: Discussionmentioning
confidence: 96%
“…Maternal PTSD symptoms have also been found to be related to PARENTAL PTSD AND CHILD ADJUSTMENT 4 increased child anxiety (Field et al, 2013). In an Australian refugee sample, the primary caregiver's severity of PTSD was found to be associated with poorer child adjustment including a higher prevalence of conduct, hyperactivity, emotional and peer problems (Bryant et al, 2018). Khamis (2016) studied refugee families settled in the U.S from the Gaza strip and found that when the influence of parent's psychological distress was controlled for, children's direct exposure to traumatic experiences was no longer associated with psychological difficulties.…”
Section: Parental Ptsd and Child Adjustmentmentioning
confidence: 99%
“…Refugee parents may work to enable their children's recovery and resilience, or their own mental health and difficulty may add to the difficulties of their children's developmental and acculturation accomplishments (Bryant et al, 2018;Measham et al, 2014). Since developmental pathways are likely to vary, it is important to know what relations and social structures are in place in the environment, and how they are interpreted and used by children and young people.…”
Section: Bases For Investigating Refugee Children's Perspectivesmentioning
confidence: 99%
“…The context and structure of children's expressions of worry are relevant to their emphases, along with the form and structure of research questions. The challenges of resettlement can pile up worrying feelings in children as well as in parents (Bryant et al, 2018;Kaplan, 2013;Montgomery, 2011). Longitudinal data are needed to determine whether school-related issues rise to greater prominence with more time in Australian schools.…”
Section: Who or What Helped Children To Feelmentioning
confidence: 99%